Studi Kekuatan Pressure Vessel Dengan Menggunakan Material SA-106 Grade B dan SA-516-70N - Silvia Uli Arta Lubis; Mufti Fathonah Muvariz; Nurul Fadilah; Naufal Abdurrahman Prasetyo; Sapto Wiratno Satoto; Nidia Yuniarsih (Jurnal Teknologi dan Riset Terapan (JATRA), 2021)
A Pressure Vessel is a container for storing liquid and gas fluid shaped like a cylinder that can produce pressure from outside or inside. Almost all oil and gas industries often use this object to collect and separate water and oil from offshore exploration. This study aims to determine the strength of a Pressure Vessel and determine which is more economical by comparing two types of materials, namely SA-106 Grade B and SA-516-70N, with the same thickness of 12.7 mm. Simulations are carried out on the shell using SolidWorks software to find out the strength of each material. The data used in this study refer to one of the Pressure Vessels from the company with the basic design following ASME section VIII Div.1 standard 2007, document name "Cartridge Filter C027-S-U13000-01 A / B" and document number 6522 -XXX-C027-ISGP-U40300-MX-4018-00XXX with a design pressure of 10 bar, a design temperature of 121 ° C, an inner diameter of 444.5 mm, a corrosion factor of 3 mm. From the calculations and simulations that have been carried out, the values ​​obtained from the maximum pressure on the SA-516-70N material are 34.10 Bar, and the SA-106 Grade B material is 16.90 Bar. The voltage received from the pressure vessel is based on the analysis of the SolidWorks software with the same value for both materials at 1758 psi / 121 Bar. This study also proved that SA-106 Grade B material is far more economical, with an estimated budget of Rp6,531,951 for one 10m long pipe.